Large Symptomatic Chorioangioma of Placenta; A Rare Complication of Pregnancy in Enugu, South East Nigeria - Henry C Nnaji; Chinyere C Molukwu; Ngozi R Dim; Nneka I Iloanusi; Cyril C Dim; Daniel B Olusina (Open Journal of Tropical Medicine - Peertechz Publications, 2018)
Chorioangioma is the most common non trophoblastic tumour of the placenta which can result to severe pregnancy complications with attendant maternal and fetal morbidity and mortality [1]. Most cases of chorioangiomas are small, microscopic and of no clinical important [2,3]. We present the very first case of large symptomatic chorioangioma managed successfully in University of Nigeria Teaching Hospital Enugu.  The patient was referred to the University of Nigeria Teaching Hospital Enugu on account of suspected symptomatic chorioangioma, at a gestational age of 32 weeks. She was managed conservatively and had elective caesarean section at 36 weeks' gestation with good outcome. There was a large solid and cystic lesion on the placenta measuring 8cm x10cm. Histological diagnosis of chorioangioma of capillary type was made.